2018
DOI: 10.1002/pro.3449
|View full text |Cite
|
Sign up to set email alerts
|

Site‐directed spin label electron paramagnetic resonance spectroscopy as a probe of conformational dynamics in the Fe(III) “locked‐off” state of the CO‐sensing transcription factor CooA

Abstract: The transcriptional activator CooA belongs to the CRP/FNR (cAMP receptor protein/fumarate and nitrate reductase) superfamily of transcriptional regulators and uses heme to sense carbon monoxide (CO). Effector-driven allosteric activation is well understood in CRP, a CooA homologue. A structural allosteric activation model for CooA exists which parallels that of CRP; however, the role of protein dynamics, which is crucial in CRP, is not well understood in CooA. We employed site-directed spin labeling electron p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…(Values between 6 and 16 nM have been reported. 18,37,38 ) It is in agreement with a high functional affinity, similar to what has been observed for the binding of RcoM-1 to the a + b + c region 14 and an efficient CO-specific recruitment of RcoM-2.…”
Section: ■ Discussionsupporting
confidence: 88%
“…(Values between 6 and 16 nM have been reported. 18,37,38 ) It is in agreement with a high functional affinity, similar to what has been observed for the binding of RcoM-1 to the a + b + c region 14 and an efficient CO-specific recruitment of RcoM-2.…”
Section: ■ Discussionsupporting
confidence: 88%
“…We demonstrated that PgRsp protein belongs to the Crp/Fnr superfamily of transcription factors and could be classified as a relatively close homolog to the CooA family. Proteins homologous to CooA can sense CO [31,53], employing interaction of CO with heme bound to the protein [51,53], thus regulating genes important for utilization of CO as an energy source [72,73]. The molecular mechanism of the best-characterized homolog of CooA protein from R. rubrum, RrCooA, implies binding of Fe(III)heme by Pro2 and Cys75, when the protein is not active.…”
Section: Discussionmentioning
confidence: 99%
“…For protein activation, the CO molecule is bound to heme by a Pro2 residue, resulting in conformational changes of the protein, leading to interaction with DNA. This kind of protein activation is unique for RrCooA protein [51][52][53], since in the CooA homolog from Carboxydothermus hydrogenoformans, the heme molecule is coordinated by Ala2 and His82 residues and no transfer of the heme group occurs during the change of iron redox state [52,73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a transcription factor or its target DNA carries a paramagnetic moiety, e.g., a spin-label or a metal center as used in PRE-NMR, direct detection of the electron spin by electron paramagnetic resonance (EPR) spectroscopy can provide valuable information complementary to NMR data [103] , [104] .…”
Section: Combining Epr and MD Simulationsmentioning
confidence: 99%